The Role of Leadership Style and Work Motivation in Improving The Performance of Production Operator Employees at PT Manufaktur Majalengka - Siregar, Fasya Amelia; Tama, Yuda; Susijawati, Noveria (Eduvest - Journal of Universal Studies, 2025)
This study explores how leadership approaches and employee motivation contribute to enhancing the job performance of production operators in a manufacturing firm based in Majalengka. The primary objective is to examine key elements that drive improved employee performance outcomes. Employing a quantitative methodology within a causal-associative framework, the research involves a total of 100 production staff members, all of whom are included as participants through a saturated sampling strategy. Data obtained from the respondents were analyzed using SmartPLS 3. The analysis revealed that both leadership style and work motivation play critical roles in shaping employee performance metrics. These insights highlight the necessity of fostering effective leadership and maintaining strong motivational levels to cultivate a more efficient and high-performing organizational environment. Management should develop and implement participative, communicative, and inspirational leadership practices to enhance employee engagement. Additionally, organizations need to design motivation enhancement programs, incorporating both financial and non-financial incentives, such as recognition, training, and career development opportunities. Consequently, employee performance can be improved sustainably, ultimately contributing to the achievement of overall organizational objectives.